ANALISIS MEKANISME PENAGIHAN PINJAMAN ONLINE (PINJOL) DITINJAU DARI PERATURAN OTORITAS JASA KEUANGAN RI NOMOR 10 /POJK.05/2022 TENTANG LAYANAN PENDANAAN BERSAMA BERBASIS TEKNOLOGI INFORMASI - Siti Nurhaliza (Bajang Institute, 2024)
The development of fintech P2P Lending in Indonesia is encouraged by the legalization of Financial Services Authority Regulation RI Number 10/Pojk.05/2022 regarding Information Technology-Based Money Lending and Borrowing Services, the regulation is a legal umbrella for Fintech P2P Lending companies in Indonesia to run their businesses. Various cases of legal violations that occur in online loans, one form of violation that often occurs in the collection process. The theory used in this study is the theory of legal certainty and the theory of legal protection, The research method uses a normative juridical approach, by examining library materials or secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Aware of the results of the study that the implementation of collection which is regulated by the Financial Services Authority Regulation and also Indonesian Joint Funding FinTech Association does not run in accordance with standard collection procedures, besides that the use of third parties, namely debt collectors, is one of the triggers for many legal violations in the online loan collection process. The online loan collection mechanism in the future is expected by the Financial Services Authority to be able to make regulations on the collection mechanism as clear and detailed as possible, In addition to regulations that must be changed, the Financial Services Authority should also not hand over authority to the association regarding activities and operational standards